STAKEHOLDERS’ PERCEPTION ON MANAGEMENT OF UPSTREAM CILIWUNG WATERSHED: IMPLICATIONS FOR FOREST LANDSCAPE PLANNING - Iis Alviya; Muhammad Zahrul Muttaqin; Elvida Yosefi Suryandari; Retno Maryani (Indonesian Journal of Forestry Research, 2017)
Forests play a vital role for the livelihoods of rural and urban communities. Addressing perception of forest users regarding forest practices is one of the most important aspects of forest management. This paper aims to elaborate stakeholders’ perception on the biophysical, socio-economic and institutional aspects of forest landscape management in upstream Ciliwung watershed.  Data were collected through survey, by highlighting preferences, perceptions, and expectations of actors who are interested in the impacts of watershed management.  This study indicates that communities at upstream Ciliwung watershed area perceived that the socio-economic aspect is the most important factor in managing upstream Ciliwung watershed.  The governments (central and local), however, pay more attention to the biophysical and institutional aspects. The result of the overall perception analysis shows that institutional aspects need to be addressed first, followed by socio-economic aspects and biophysical aspects to improve the management of upstream Ciliwung watershed.  Addressing institutional aspects is needed to enhance awareness and coordination among stakeholders, to enforce law and to develop a monitoring system to support the preservation of the forest at the upstream watershed areas. In terms of socio-economic aspects, improving community livelihoods is needed through payments for environmental services. Regarding biophysical aspects, afforestation and conservation of soil and water need to be prioritised. Thus, there should be programs that could provide solutions based on the three main aspects to improve the management of the forest resources in the upstream watershed area.